(untitled) (Research, Society and Development, 2022)
This research aimed to investigate, through an integrative literature review, the practice of physical activity by university students to reduce symptoms of depression. The research was carried out in 2016 and has historical interest. Five databases were used: MedLine (PubMed), Scopus, PsyINFO, VHL and Scielo. With the descriptors: “depress* AND student* (OR colleg*) AND physic* AND activit* (OR exercise*)”. 622 scientific investigations were found, 109 (17.52%) in the MedLine database (PubMed), 251 (40.35%) in Scopus, 23 (3.7%) in PsyInfo, 228 (36.65%) in BVS and 11 (1.7%) at Scielo. After analysis and removal the 46 remaining investigations were grouped into five categories and discussed. Our results indicate that little research has been done on the obstacles to physical activity in university students with signs of depression. However, the association between physical activity/exercise and positive mental health in university students is widely investigated and many authors describe a negative correlation between these variables. In this context, our results point to the benefit of different types of body activities with different training programs, as long as they are performed under proper guidance, especially when performed intensively. It is worth remembering that none of the investigations present in this review used a descriptive qualitative methodology, which points to a lack of information on particular aspects in relation to these subjects and the universities where they carry out their studies. It is hoped that our results can help health professionals, especially those in physical education, in prescribing physical activity/exercise within universities as a complementary treatment to psychotherapeutic and/or medication for depression.